“Media Use and the Analytical Brain”: Screen-Based Media Use and Behavioral Preference in Indonesian Children: [“Penggunaan Media dan Otak Analitik”: Penggunaan Media Berbasis Layar dan Preferensi Perilaku Anak Indonesia] - Kesumaningsari, Ni Putu Adelia; Stauder, Johannes E. A.; Donkers, Franc C. L. (Faculty of Psychology, Universitas Surabaya, 2023)
This study aims to examine the relationship between screen-based media use and autistic features. The present study involved 207 parents of Indonesian children 4-6 years old and 10-12 years old. Parents completed several questionnaires addressing children screen-based activities and level of autistic traits. The questionnaires are: (1) a screen-based media survey; (2) Empathizing-Systemizing Quotients (EQ-SQ Child); and (3) The Autism Spectrum Quotient (AQ-Child). An online survey was utilized to collect all study data. The results showed that children spent more than four hours on average per day with media use. The regression analysis indicated that total time spent by children on media use shows a positive correlation with systemizing. The total time spent by children on media use also positively correlated with the extreme male brain condition. The total time spent on screen-based media use did not significantly contribute to explaining the variance of empathizing. However, empathizing is negatively correlated with time devoted in watching activities (television, videos, and movies) and playing video games. The more children spend time playing in video games, the more the autism quotient (AQ) score increases. Finally, the current study provides empirical evidence for a relation of screen-based media use and autistic features in children. The findings suggest that the duration of screen-time are significant predictors of systemizing and extreme male behavior, albeit the significance for empathizing depends on the type of media. The results highlight the clinical importance of examining screen-based media use among children. Studi ini bertujuan untuk menguji hubungan antara penggunaan media berbasis layar dengan karakteristik autisme. Studi ini melibatkan 207 orang tua di Indonesia yang memiliki anak berusia 4-6 tahun dan 10-12 tahun. Orang tua menyelesaikan beberapa survei secara daring. Kuesioner tersebut terdiri dari: (1) survei mengenai durasi penggunaan media berbasis layar pada anak; (2) skala Empathizing-Systemizing Quotient (EQ-SQ Child); dan (3) skala Autism Spectrum Quotient (AQ-Child). Hasil studi menunjukkan bahwa anak menghabiskan waktu secara rerata lebih dari empat jam per hari dengan penggunaan media. Analisis regresi menunjukkan bahwa durasi total penggunaan media berkorelasi positif dengan tingkat sistemisasi anak dan extreme male brain behavior, namun tidak berkontribusi secara signifikan dalam menjelaskan tingkat empati anak. Tingkat empati secara spesifik berkorelasi negatif dengan waktu yang digunakan untuk aktivitas menonton (televisi, video, dan film) dan bermain video game. Semakin lama durasi anak bermain video game, maka skor autism quotient (AQ) juga meningkat. Dengan demikian, studi ini memberikan bukti empiris mengenai hubungan penggunaan media berbasis layar dengan karakteristik autisme pada anak. Durasi penggunaan media berbasis layar adalah prediktor yang siginifikan untuk tingkat sistemasi dan extreme male brain behavior, sedangkan tingkat berempati anak lebih dipengaruhi oleh jenis media. Hasil studi ini menyoroti pentingnya memperhatikan dampak dari penggunaan media berbasis layar pada anak.